2009
DOI: 10.1534/genetics.108.093229
|View full text |Cite
|
Sign up to set email alerts
|

The Control Region of Maternally and Paternally Inherited Mitochondrial Genomes of Three Species of the Sea Mussel Genus Mytilus

Abstract: Species of the mussel genus Mytilus possess maternally and paternally transmitted mitochondrial genomes. In the interbreeding taxa Mytilus edulis and M. galloprovincialis, several genomes of both types have been fully sequenced. The genome consists of the coding part (which, in addition to protein and RNA genes, contains several small noncoding sequences) and the main control region (CR), which in turn consists of three distinct parts: the first variable (VD1), the conserved (CD), and the second variable (VD2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 45 publications
7
49
0
Order By: Relevance
“…In contrast, the first and last domains are among the most divergent parts of the M and F genomes. It has been suggested that this tripartite structure, which is also a characteristic of the mammalian control region, demonstrates that different parts of the control region evolve under different selective constraints (Cao et al 2004a(Cao et al , 2009). In freshwater mussels (Unionoida), the high degree of sequence divergence observed among species and also between intraspecific F and M genomes presents a challenge for characterizing the structure of any of the shared unassigned regions.…”
Section: Regions B C and A)mentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, the first and last domains are among the most divergent parts of the M and F genomes. It has been suggested that this tripartite structure, which is also a characteristic of the mammalian control region, demonstrates that different parts of the control region evolve under different selective constraints (Cao et al 2004a(Cao et al , 2009). In freshwater mussels (Unionoida), the high degree of sequence divergence observed among species and also between intraspecific F and M genomes presents a challenge for characterizing the structure of any of the shared unassigned regions.…”
Section: Regions B C and A)mentioning
confidence: 96%
“…For the more distantly related species, pairwise comparisons within each gender revealed, as expected, higher levels of nucleotide sequence divergence (.45%). Identification of conserved motifs or regions with high similarity to the other DUI-species control regions: Previous analyses of the mytiloid mussel Mytilus have shown that the F and M main control regions can be divided into three domains on the basis of indels and patterns of nucleotide variation (Cao et al 2004a(Cao et al , 2009). The middle domain of the control region encodes a hairpin structure and is the most slowly evolving part of the mitochondrial genome.…”
Section: Regions B C and A)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the class Bivalvia, there are five genera which have at least two complete genomes reported, hongkongensis, C. iredalei, C. nippona, C. sikamea and C. virginica) were obtained from GenBank Breton et al, 2006;Cao et al, 2009;He et al, 2011;Milbury and Gaffney, 2005;Mizi et al, 2005;Ren et al, 2009a;Ren et al, 2009b;Wang et al, 2010;Wang et al, 2011;Wu et al, 2010;Xu et al, 2012;Yu and Li, 2011;Yuan et al, 2012). In addition to the mitochondrial genome sequence of M. chinensis from this study, the three recent reported mitochondrial genomes from Mactra veneriformis and Coelomactra antiquata (two genomes from the latter with specimens from Ri Zhao, Shandong Province in northern China and Zhang Zhou, Fujian Province in southern China) (Meng et al, 2013a;Meng et al, 2012;Meng et al, 2013c) were included in the phylogenetic analysis which includes a total of 25 bivalve mitochondrial genomes.…”
Section: Genetic Distance and Phylogenetic Analysis Within Bivalviamentioning
confidence: 99%